Shifts in dissolved organic matter and nutrients in tundra ponds along a gradient of permafrost erosion - Pacoureau, Thomas; Mazoyer, Flora; Maranger, Roxane; Rautio, Milla; Laurion, Isabelle (Arctic science, 2025)
The accelerated thawing of permafrost in ice-wedge polygonal landscapes results in the formation of shallow ponds, where nutrients and dissolved organic matter (DOM) remain poorly characterized. Over three consecutive summers, water was collected from a series of ponds on degrading syngenetic permafrost, representing the most common geomorphological categories: erosive or stable ice-wedge trough ponds and coalescent polygon ponds. Dissolved organic carbon (DOC) and nutrients were quantified, and DOM was characterized using optical analysis. These ponds were rich in carbon and nutrients, particularly the ice-wedge trough ponds with eroding permafrost. They also exhibited higher concentrations of DOC (+25% on average), total nitrogen (+36%), ammonium (+1164%), and total phosphorus (+108%) in the hypolimnion compared to the epilimnion. DOM was mainly of terrestrial origin (57%–75% of total fluorescent DOM), though protein-like fluorescent components increased in ponds colonized by vegetation and cyanobacterial mats. Weather conditions significantly influenced DOC (+26% in a wet and warm year) and DOM composition in summer, with warmer temperatures and higher precipitation enhancing lateral DOM transfer from permafrost soils and promoting contributions from cyanobacterial mats. These findings improve the understanding of Arctic pond biogeochemistry, enabling a more accurate assessment of their potential role in climate feedback mechanisms.